2021
DOI: 10.3389/fimmu.2020.624199
|View full text |Cite
|
Sign up to set email alerts
|

Discipline in Stages: Regulating CD8+ Resident Memory T Cells

Abstract: Resident memory CD8+ T (TRM) cells are a lymphocyte lineage distinct from circulating memory CD8+ T cells. TRM lodge within peripheral tissues and secondary lymphoid organs where they provide rapid, local protection from pathogens and control tumor growth. However, dysregulation of CD8+ TRM formation and/or activation may contribute to the pathogenesis of autoimmune diseases. Intrinsic mechanisms, including transcriptional networks and inhibitory checkpoint receptors control TRM differentiation and response. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 168 publications
(268 reference statements)
0
7
0
Order By: Relevance
“…A crucial role for TGF-β in tissue retention of Trm has been shown in multiple tissues, including skin and gut [31,51,60]. In fact, TGF-β signaling induces CD103 expression and promotes Trm maintenance across organs [43]. Zhang et al reported two distinct functions for TGF-β signaling during the formation and maintenance of intestinal Trm in a model of systemic infection with the LCMV strains Armstrong (Arm) and Clone 13, which promote acute and chronic infection, respectively.…”
Section: Cytokinesmentioning
confidence: 99%
See 3 more Smart Citations
“…A crucial role for TGF-β in tissue retention of Trm has been shown in multiple tissues, including skin and gut [31,51,60]. In fact, TGF-β signaling induces CD103 expression and promotes Trm maintenance across organs [43]. Zhang et al reported two distinct functions for TGF-β signaling during the formation and maintenance of intestinal Trm in a model of systemic infection with the LCMV strains Armstrong (Arm) and Clone 13, which promote acute and chronic infection, respectively.…”
Section: Cytokinesmentioning
confidence: 99%
“…CD49a (Integrin β1, or very late antigen 1 (VLA1)), a subunit of the collagen receptor α1β1, is also well‐known to favor Trm maintenance in epithelial tissues such as the skin by binding to type I and IV‐ collagen [ 43 ], and was found to be up‐regulated in human gut Trm [ 44 ] and necessary for maintenance of Trm in the SI epithelium in mice [ 45 ].…”
Section: Migration and Homing Markers Of Intestinal T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD8 + Trm cells mainly reside on the barrier epithelium of nonlymphoid organs and respond rapidly to both viral and bacterial infection and tumorigenesis. In human digestive tract mucosa, CD8 + Trm cells play a key role in anti-infection and antitumor immunity because they elicit a rapid immune response after antigen stimulation (7) .…”
Section: Introductionmentioning
confidence: 99%